Lauret-7-Sitrat sebagai Detergensia dan Peningkat Busa pada Sabun Cair Wajah Glysine soja (Sieb.) Zucc - SITI UMRAH NOOR; DESY NURDYASTUTI (Fakultas Farmasi Universitas Pancasila, 2009)
Soya milk is an extraction product from soya bean that can be used as humectant due to its amino acids which are similar to those in our skin, such as glycine, serine, alanine, asparagine, ornithine, citruline, proline, and 17 other amino acids. ln this study, a liquid facial Wash containing soya milk using lauret-7-citrate (concentration 0, 1, 2, and 3%) was formulated that could affect the surface active characteristis, and the foam formation. The organoleptic characteristics, density, viscosity, rheology, surface tension, foam height and stability of foam height in pure and hard Water were determined at 25°C and 40°C for 8 Weeks. The results obtained showed that the best facial Wash was that contained 15% soya milk (2% lauret-7-citrate) of which had the following properties: a pseudoplastic rheology, a density of 1.076-l.079 g/cm3, a viscosity of 14,550-17,300 cPs, a surface tension of 25.41-27.18 dyne/ cm3, foam height in pure Water of 850-866.67 ml and in hard Water 466.67-600 ml, and stable at pH 4.99-5.00.